Leadership and digital change : the digitalization paradox - Iveroth, Einar; Hallencreutz, Jacob (New York, NY: Routledge, 2021)
"Digitalization is on everyone's lips as new technology changes business landscapes and conventional companies are outperformed by younger digital and agile contestants. In this volatile environment it seems more relevant than ever before to understand the aspects and business logic behind the elusive phenomenon called "digitalization". Never before have there been such great opportunities to unleash the full potential of technology within organizations to create long-standing competitive advantage. This book explains the strategy and practice of how to lead and control the people side of digital change in a dynamic world of uncertainty and social complexity, and as such the book snares the elusive phenomena of digitalization Digitalization drives behavioral change and calls for a new way of thinking among senior executives. In practice, reaping the benefits of digital technology is not as easy as it first appears to be. This book provides a map to navigate in the volatile business landscape where change occurs continuously because of digital technology. It provides an historical frame of the evolution of digital technology, decodes digitalization's negative influence on the external aspects of customer satisfaction, discusses and explains the strategic and leadership consequences of different forms of digital change, and finally demonstrates how leading digital change can be put into practice. Illustrative case studies and examples are provided throughout as well as models and frameworks. This is a valuable resource for researchers, academics, and students in the fields of organizational studies, organizational change, technology & innovation management, and digitalization"--Provided by publisher.
Includes bibliographical references and index
Keywords: Information technology -- -- Management; Industrial management -- -- Technological innovations; Organizational change; Leadership